Effects of fluoride and aluminum on expressions of StAR and P450scc of related steroidogenesis in guinea pigs' testis. (March 2016) - Dong, Chunguang; Cao, Jinling; Cao, Chunfang; Han, Yichao; Wu, Shouyan; Wang, Shaolin; Wang, Jundong
Abstract: A lot of studies have shown that fluoride and aluminum have toxic effect on male reproductive system, but the mechanism of which and the interaction between fluoride and aluminum is still unknown. This study investigated the effects of fluoride (NaF) or/and aluminum (AlCl3 ) on serum testosterone level, gene and protein expression levels of Steroidogenic Acute Regulatory Protein ( StAR ) and Cytochrome P450 cholesterol side chain cleavage enzyme ( P450scc ) in the testes of guinea pigs. Fifty-two guinea pigs were divided randomly into four groups (Control, HiF, HiAl and HiF + HiAl). Fluoride (150 mg NaF/L) or/and aluminum (300 mg AlCl3 /L) were orally administrated to male guinea pigs for 13 weeks. The results showed that F and Al reduced number and elevated abnormal ratio of sperm. Meanwhile, the concentrations of serum testosterone in all experimental groups were decreased. P450scc protein expression was significantly reduced in all treatment groups, and StAR expression was decreased remarkably in HiF group and HiF + HiAl group. The levels of StAR mRNA in three groups were reduced by 53.9%, 21.4% and 33.4%, respectively, while the expressions of P450scc mRNA were reduced by 67.8%, 17.0% and 47.8%. Therefore, we concluded that F induced the reduction in testosterone and sperm amount, and thus in lower fertility, which might occur as a consequence of depressed StAR and P450scc mRNA expression. There were no synergistic effects between F and Al, instead, Al weakened the toxicity of F to some extents. The results indicated that Al had antagonism effects on F. Highlights: F and Al changed histological structure of testes, reduced sperm quality. F and Al reduced StAR and P450scc expressions and level of serum testosterone. F toxicity is stronger than Al and Al weakened the toxicity of F. Al had antagonism effects on F.